ANALISIS KESANTUNAN BERBAHASA PADA AKUN TIKTOK @IAMEGAMEI: ORANG INDIA, BUKAN VRINDAVAN ATAU PRIDAPAN - Khilyaturrahmah, Irma; Romadona, Devi Ayu Dwi; Dewi, Mirna Layli; Ningsih, Nurul Karina; Utomo, Asep Purwo Yudi (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
Language politeness is the values of courtesy or ethics when speaking that is contained in social rules of society. Language politeness plays an important role in communication because in communicating speakers not only pronounce the sounds of the language, but also ensures that the speech can be accepted by speech partners. Therefore, research on linguistic politeness is interesting to do, especially language politeness in social media that is widely accessed by the public, one of which is TikTok channel. This research was conducted to identify the principles of language politeness in 2 minutes 46 seconds video on @iamegamei's TikTok channel. The video criticizes the labeling of Indians as Vrindavan or Prindapan with negative connotations that are often done by Indonesian netizens. This research method uses descriptive qualitative pragmatic method with observing and note-taking techniques. Then data is analyzed by using a pragmatic equivalent method. From the research that have been conducted, it is found that the obedience and violation of language politeness thimbles. However, thimble violations dominate, causing language impoliteness in the TikTok video of @iamegamei's account.